Pengaruh Fungsi Keluarga, Dukungan Sosial, dan Beban Perawatan terhadap Ketahanan Keluarga yang tinggal bersama Lansia - Siska Ayu Tiara Dewi; Tin Herawati; Istiqlaliyah Muflikhati (Jurnal Sosial Humaniora, 2024)
As Indonesia enters the era of an aging society, protecting the elderly becomesincreasingly important, particularly for family members who serve as primarycaregivers. This study aims to analyze the impact of family characteristics,elderly characteristics, family functions, social support, and caregivingburden on family resilience. The research sample consisted of families withelderly members in the household, focusing specifically on wives asrespondents in the Kemang District, Bogor Regency. We collected datathrough direct interviews with 120 respondents and analyzed them usingdescriptive and inferential statistical methods. The findings reveal that familyfunction and social support have a significant and positive impact on familyresilience. These factors contribute to the family's ability to adapt, cope, andmaintain stability despite the challenges of caring for elderly members.Conversely, the burden of caregiving has a significant negative impact onfamily resilience, indicating that higher caregiving demands can strain familyresources and emotional well-being. This study underscores the importance ofstrengthening family functions and enhancing social support systems tobolster family resilience in the face of aging-related challenges. Addressingthese factors can help to improve the quality of care for the elderly and supportthe well-being of families in Indonesia's aging society.